Social Sector Reform in Latin America and the Role of Unions - Daniel Maceira; Maria Victoria Murillo (Inter-American Development Bank, Research Department, 2001)
This paper analyzes the reaction of teachers` and doctors` unions to a series of social sector reforms in the region, including administrative decentralization, provider payment mechanisms, and the introduction of performance evaluation and private provision. It combines the literature of economics and political science to understand the conditions that shape different patterns of union behavior and their effect on policy implementation. The paper suggests that the main conditions influencing union behavior in the health sector are related to the structure of the market (size and level of competition) due to the predominance of the private-public mix in its employment. In education, where the public sector is the main employer, political alignments and the organizational features of teachers` associations also play an important role in explaining the behavior of providers` organizations. Considering the exogenous character of most of these variables, the paper concludes by making some policy suggestions to align the objectives of unions and policymakers through regulatory reforms.
Keywords: 330; Bildungsreform; Gesundheitsreform; Dienstleistungsqualität; Marktstruktur; Gewerkschaft; Lateinamerika